The South Korean film industry and the Chinese film market - Lee, Sangjoon (2020)
On 26 August 2016, the South Korea–Thailand–China co-production P'ainŏl Reship'i//Final Recipe (Gina Kim, 2014) opened on 3200 screens across the People’s Republic of China. The film was the first South Korean-directed feature to be granted a wide release in China following the 2014 South Korea–China Free Trade Agreement (FTA). Final Recipe featured the Malaysian Michelle Yeoh, the Singaporean Chin Han and the K-pop superstar Henry Lau (a Taiwanese American), and was shot in Bangkok, Seoul and Shanghai. The film tells the story of a high-school student (Lau) who enters a MasterChef-type cooking competition and finds his long-lost father along the way. Final Recipe is one of many attempts made by the South Korean media giant CJ E&M (hereafter CJ) to break into the global film market. Led by the company’s US-born executive Miky Lee (Yi Mi-kyŏng), CJ’s ‘global project’ has an ambitious vision of broadening the horizons of international co-productions and using English-language scripts and transnational casts to increase its films’ global appeal. Following this strategy, CJ planned to target the company’s emerging markets in Southeast Asia and China with Final Recipe’s ‘all English-speaking’ Asian cast. Given the popularity of food-related films in Asia, Final Recipe’s box-office forecast in the Chinese market was positive. Hallyu, the Korean pop culture wave, has triggered numerous trends across Asia, and China has become the biggest market for the hallyu industry. The culmination of this wave was the South Korean television drama T'aeyang ŭi huye/Descendants of the Sun (2016), broadcast simultaneously in South Korea and China only months before the release of Final Recipe in China. The last episode of Descendants of the Sun was viewed a record-breaking 2.4 billion times on the online video platform iQiYi in April 2016.